The Influence of Parenting Styleson Children's Introverted Personalities - Syamsudin, Syamsudin; Helena, Helena; Faslah, Roni; Az-Zahra, Dwi Wahyuni (Ahlussunnah: Journal of Islamic Education, 2025)
The tendency of children to have introverted personalities is influenced by the parenting styles of their parents within the family environment. This study aims to determine the influence of authoritarian, democratic, and permissive parenting styles on children's introverted personalities. The method used was a quantitative statistical approach through a Likert scale questionnaire administered to 12 parents who were selected as samples based on purposive sampling. Data analysis was performed using multiple linear regression with the help of the Statistical Package for the Social Sciences. The results showed that the three types of parenting styles did not have a significant effect on children's introverted personalities (significance value > 0.05). Authoritarian and permissive parenting styles showed a positive relationship, while democratic parenting showed a negative relationship with introverted tendencies, but this was not statistically significant. The results of this study indicate that the formation of a child's introverted personality is not only influenced by parenting styles, but also by internal factors such as innate temperament, as well as external factors such as the social environment, emotional experiences, and the surrounding culture, which also have a significant influence. Parenting styles should be based on gentleness, wisdom, and exemplary behavior as described in the letter of Luqman. Parents need to understand that introverted children are not to be corrected, but to be understood and guided with love. Therefore, a spiritual, reflective, and respectful approach to parenting is key in accompanying their growth and development